2009
DOI: 10.1101/gr.093302.109
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping of alternative splicing in Arabidopsis thaliana

Abstract: Alternative splicing can enhance transcriptome plasticity and proteome diversity. In plants, alternative splicing can be manifested at different developmental stages, and is frequently associated with specific tissue types or environmental conditions such as abiotic stress. We mapped the Arabidopsis transcriptome at single-base resolution using the Illumina platform for ultrahigh-throughput RNA sequencing (RNA-seq). Deep transcriptome sequencing confirmed a majority of annotated introns and identified thousand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

80
927
6
8

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 840 publications
(1,043 citation statements)
references
References 75 publications
80
927
6
8
Order By: Relevance
“…Retained intron, in which a single intron is alternatively included or spliced out of the mature mRNA via an intron-definition splicing mechanism, was the most prevalent type of AS event (30.4%; Fig. 3C), consistent with previous studies in plants (Black, 2003;Wang and Brendel, 2006;Barbazuk et al, 2008;Filichkin et al, 2010;Li et al, 2010;Lu et al, 2010;Zhang et al, 2010;Marquez et al, 2012) but in contrast to animal AS events, where exon skipping (cassette exons or coordinate cassette exons) is the predominant mechanism (Sultan et al, 2008;Wang et al, 2008;Daines et al, 2011;Graveley et al, 2011). Furthermore, alternative 39 splice sites (A3SS; 21.0%) or alternative last exons (ALE; 11.5%) and alternative 59 splice sites (A5SS; 12.2%) or alternative first exons (AFE; 11.7%) were other types of common AS events observed in our data (Fig.…”
Section: As Is Differentially Regulated Between Embryo and Endospermsupporting
confidence: 79%
See 3 more Smart Citations
“…Retained intron, in which a single intron is alternatively included or spliced out of the mature mRNA via an intron-definition splicing mechanism, was the most prevalent type of AS event (30.4%; Fig. 3C), consistent with previous studies in plants (Black, 2003;Wang and Brendel, 2006;Barbazuk et al, 2008;Filichkin et al, 2010;Li et al, 2010;Lu et al, 2010;Zhang et al, 2010;Marquez et al, 2012) but in contrast to animal AS events, where exon skipping (cassette exons or coordinate cassette exons) is the predominant mechanism (Sultan et al, 2008;Wang et al, 2008;Daines et al, 2011;Graveley et al, 2011). Furthermore, alternative 39 splice sites (A3SS; 21.0%) or alternative last exons (ALE; 11.5%) and alternative 59 splice sites (A5SS; 12.2%) or alternative first exons (AFE; 11.7%) were other types of common AS events observed in our data (Fig.…”
Section: As Is Differentially Regulated Between Embryo and Endospermsupporting
confidence: 79%
“…For example, the Arabidopsis TF gene IDD14 generates two splicing variants to competitively form nonfunctional heterodimers to regulate starch metabolism (Seo et al, 2011). In our RNA-seq data of maize embryo and endosperm, 50.7% of multiexonic genes were found to undergo AS, which is higher than that in Arabidopsis and rice (Filichkin et al, 2010;Lu et al, 2010). This indicates that the splicing diversity of the maize transcriptome is more complex than that in Arabidopsis and rice.…”
Section: Embryo and Endosperm Exhibit Differential As Patternsmentioning
confidence: 56%
See 2 more Smart Citations
“…Instead, Li et al (2016) observed that intron retention is the major type of AS in root tissues (>41%), in agreement with previous findings (Filichkin et al, 2010), followed by alternative acceptor (<26%) and alternative donor (>12%) splicing variants. The authors classified intron retention events as either type I (where the major isoform excises the intron) or type II (where the major isoform retains the intron).…”
Section: Resolution Expression Map Of As Events In Arabidopsis Root Tsupporting
confidence: 87%